Isolation and characterization of chitinase from soil fungi, Paecilomyces sp. - Homthong, Methanee; Kubera, Anchanee; Srihuttagum, Matana; Hongtrakul, Vipa (Agriculture and Natural Resources, 2016)
Chitinolytic fungal strains were isolated from soil in Thailand. They were screened as chitinase producers by testing their shrimp shell digestion ability on potato dextrose agar plates. The chitinase activity was tested with colloidal chitin in culture medium C and basal medium. There was greater activity in culture medium C than in the basal medium. The results of sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis from the culture filtrate of medium C showed three protein bands at about 40 kDa, 46 kDa and 56 kDa. The chitinase gene was sequenced from genomic DNA. The obtained sequence consisted of 713 bp upstream, a 1499 bp open reading frame that was interrupted by three introns and 1698 bp downstream sequences. The intron lengths were 63 bp, 57 bp and 110 bp, respectively. The sequence was found to be the most similar to the chitinase gene of Paecilomyces lilacinus (EF183511). Pairwise alignment of the 1499 bp and P. lilacinus resulted in 72.5% DNA sequence identity, while alignment of the 1269 bp coding sequence and P. lilacinus resulted in 78.5% cDNA sequence identity and 83.5% amino acid sequence identity. The protein structure contained two conserved domains of the putative substrate binding site (S-I-G-G) and catalytic domain (D-G-I-D-L-D-W-E), suggesting that this fungal chitinase belonged to the glycosyl hydrolases family 18 chitinase (GH18). Phylogenetic analysis of the chitinase gene from the nematopathogenic fungi suggested that this chitinase sequence was class V chitinase.